Lateral Condyle Fracture of the Humerus in Children: Kirschner Wire or Screw Fixation? - Wendling-Keim, Danielle S.; Teschemacher, Sandra; Dietz, Hans-Georg; Lehner, Markus (European Journal of Pediatric Surgery, 2020)
Introduction The treatment of the displaced fracture of the lateral condyle of the distal humerus in children aims not only to avoid nonunion, malalignment, and impairment of the range of motion of the elbow but also to prevent delayed healing and the development of any prearthrotic deformity. To date there is no agreement on what kind of osteosynthesis should be used. So far, the screw fixation and Kirschner wire fixation have both been applied. Therefore, the goal of this study was to compare the outcome of these two methods.Materials and Methods A retrospective cohort study was undertaken including 43 patients aged 2 to 13 years who underwent osteosynthesis for a condylar fracture of the humerus over a period of 10 years. The electronic archive, including the radiological diagnostics, was analyzed. Statistical analysis was performed using IBM SPSS Statistics 20.0. Statistical significance was set at an α level of p = 0.05.Results Kirschner wire fixation was performed in 48.9% of condylar fractures of the humerus while screw fixation (alone or in combination with a pin) was assessed with a percentage of 51.1% of the cases in this study. Screw fixation only was applied in 20.9% of fractures of the lateral condyle. The selection of the method was independent of the age of the patient (p = 0.2). The comparison of the rate of complications and an impaired range of motion after Kirschner wire osteosynthesis to the rate after screw osteosynthesis showed a significantly lower percentage for the Kirschner wire group (p = 0.046). No case of nonunion, nerve palsy, or pin migration was detected in any patient in this study.Conclusion Kirschner wire fixation of condylar humeral fractures in children resulted in a lower rate of complications than screw fixation. No case of nonunion of the fracture was found in the patients that we investigated so that we conclude that Kirschner wires sufficiently adapt the fracture in these cases.Level of Evidence Level III.
Keywords: screw fixation; pin fixation; children; lateral condyle fracture of the humerus